Shifting sand : journal of a cub archaeologist, Palestine 1964 - Berry, Julian, 1946- (Archaeological lives., 2017)
'Shifting Sand' is the journal of Julian Berry, then a 17-year-old archaeologist, written on-site during excavations in Jordan, 1964. The book provides a fascinating insight into the lives of archaeologists over 50 years ago, and the very close links between the European team, the Arab workmen, and the daily life in a simple mud-brick village.